Techno-Economic Analyses of the CaO/CaCO3 Post-Combustion CO2 Capture From NGCC Power Plants - Fu, Chao; Roussanaly, Simon; Jordal, Kristin; Anantharaman, Rahul (Frontiers in Chemical Engineering, 2021)
Calcium looping is a post-combustion technology that enables CO2 capture from the flue gases of industrial processes. While considerable studies have been performed at various levels from fundamental reaction kinetics to the overall plant efficiency, research work on techno-economic analyses of the calcium looping processes is quite limited, particularly for the Natural Gas Combined Cycle (NGCC). Earlier work has shown that theoretically, a high thermal efficiency can be obtained when integrating calcium looping in the NGCC using advanced process configurations and a synthetic CaO sorbent. This paper presents an investigation of calcium looping capture for the NGCC through a techno-economic study. One simple and one advanced calcium looping processes for CO2 capture from NGCC are evaluated. Detailed sizing of non-conventional equipment such as the carbonator/calciner and the solid-solid heat exchanger are performed for cost analyses. The study shows that the CO2 avoided cost is 86-95 €/tCO2,avoided, which is considerably more expensive than the reference amine (MEA) capture system (49 €/tCO2,avoided). The calcium looping processes considered have thus been found not to be competitive with the reference MEA process for CO2 capture from NGCC with the inputs assumed in this work. Significant improvements would be required, for example, in terms of equipment capital cost, plant efficiency and sorbent annual cost in order to be make the calcium looping technology more attractive for capturing CO2 from NGCC plants.